Outcomes in liver transplant recipients with nonalcoholic fatty liver disease-related HCC: results from the US multicenter HCC transplant consortium. Issue 1 (23rd January 2023) - Verna, Elizabeth C.; Phipps, Meaghan M.; Halazun, Karim J.; Markovic, Daniela; Florman, Sander S.; Haydel, Brandy M.; Ruiz, Richard; Klintmalm, Goran; Lee, David D.; Taner, Burcin; Hoteit, Maarouf A.; Tevar, Amit D.; et al.
Abstract : NAFLD will soon be the most common indication for liver transplantation (LT). In NAFLD, HCC may occur at earlier stages of fibrosis and present with more advanced tumor stage, raising concern for aggressive disease. Thus, adult LT recipients with HCC from 20 US centers transplanted between 2002 and 2013 were analyzed to determine whether NAFLD impacts recurrence-free post-LT survival. Five hundred and thirty-eight (10.8%) of 4981 total patients had NAFLD. Patients with NAFLD were significantly older (63 vs. 58, p <0.001), had higher body mass index (30.5 vs. 27.4, p <0.001), and were more likely to have diabetes (57.3% vs. 28.8%, p <0.001). Patients with NAFLD were less likely to receive pre-LT locoregional therapy (63.6% vs. 72.9%, p <0.001), had higher median lab MELD (15 vs. 13, p <0.001) and neutrophil-lymphocyte ratio (3.8 vs. 2.9, p <0.001), and were more likely to have their maximum pre-LT alpha fetoprotein at time of LT (44.1% vs. 36.1%, p <0.001). NAFLD patients were more likely to have an incidental HCC on explant (19.4% vs. 10.4%, p <0.001); however, explant characteristics including tumor differentiation and vascular invasion were not different between groups. Comparing NAFLD and non-NAFLD patients, the 1, 3, and 5-year cumulative incidence of recurrence (3.1%, 9.1%, 11.5% vs. 4.9%, 10.1%, 12.6%, p =0.36) and recurrence-free survival rates (87%, 76%, and 67% vs. 87%, 75%, and 67%, p =0.97) were not different. In competing risks analysis, NAFLD did not significantly impact recurrence in univariable (HR: 0.88, p =0.36) nor in adjusted analysis (HR: 0.91, p =0.49). With NAFLD among the most common causes of HCC and poised to become the leading indication for LT, a better understanding of disease-specific models to predict recurrence is needed. In this NAFLD cohort, incidental HCCs were common, raising concerns about early detection. However, despite less locoregional therapy and high neutrophil-lymphocyte ratio, explant tumor characteristics and post-transplant recurrence-free survival were not different compared to non-NAFLD patients.